BRAF/MAPK and GSK3 signalling converge to control MITF nuclear export - Goding, C; Ngeow, KC; Friedrichsen, HJ; Li, L; Zeng, Z; Andrews, S; Berridge, G; Picaud, S; Fischer, R; Lisle, R; Knapp, S; Filippakopoulos, P; et al. (National Academy of Sciences, 2018)
The close integration of the MAPK, PI3K, and WNT signaling pathways underpins much of development and is deregulated in cancer. In principle, combinatorial posttranslational modification of key lineage-specific transcription factors would be an effective means to integrate critical signaling events. Understanding how this might be achieved is central to deciphering the impact of microenvironmental cues in development and disease. The microphthalmia-associated transcription factor MITF plays a crucial role in the development of melanocytes, the retinal pigment epithelium, osteoclasts, and mast cells and acts as a lineage survival oncogene in melanoma. MITF coordinates survival, differentiation, cell-cycle progression, cell migration, metabolism, and lysosome biogenesis. However, how the activity of this key transcription factor is controlled remains poorly understood. Here, we show that GSK3, downstream from both the PI3K and Wnt pathways, and BRAF/MAPK signaling converges to control MITF nuclear export. Phosphorylation of the melanocyte MITF-M isoform in response to BRAF/MAPK signaling primes for phosphorylation by GSK3, a kinase inhibited by both PI3K and Wnt signaling. Dual phosphorylation, but not monophosphorylation, then promotes MITF nuclear export by activating a previously unrecognized hydrophobic export signal. Nonmelanocyte MITF isoforms exhibit poor regulation by MAPK signaling, but instead their export is controlled by mTOR. We uncover here an unanticipated mode of MITF regulation that integrates the output of key developmental and cancer-associated signaling pathways to gate MITF flux through the import–export cycle. The results have significant implications for our understanding of melanoma progression and stem cell renewal.